2019
DOI: 10.1007/s10964-019-01155-3
|View full text |Cite
|
Sign up to set email alerts
|

How do Adolescents’ Perceptions of Relationships with Teachers Change during Upper-Secondary School Years?

Abstract: The student-teacher relationship has mostly been assumed to be static. This approach is limited in providing information on how relationships with teachers evolve over time, and how possible changes affect young people's adjustment. To address this gap in knowledge, the present study examined whether adolescents follow different trajectories in their perceptions of relationship with teachers and whether students on different trajectories differ from each other in their adjustment. The sample included 829 stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
4
12
0
Order By: Relevance
“…We found that older students reported weaker positive school relations and poorer mental health, along with a higher incidence of negative school relations. These findings are consistent with previous studies that have identified declines over time in adolescents' mental health outcomes as well as in their perceptions of emotional support from teachers (Eccles and Roeser, 2011;Bayram Özdemir and Özdemir, 2020). Given that adolescence is a major life period marked by numerous individual and contextual challenges with the potential to impact on adolescents' mental health (Dwivedi and Harper, 2004;Grazzani Gavazzi et al, 2011), our results add to our understanding of the association between school relations and mental health across age groups, confirming that student mental health hits its lowest point during late adolescence.…”
Section: Age Invariancesupporting
confidence: 92%
“…We found that older students reported weaker positive school relations and poorer mental health, along with a higher incidence of negative school relations. These findings are consistent with previous studies that have identified declines over time in adolescents' mental health outcomes as well as in their perceptions of emotional support from teachers (Eccles and Roeser, 2011;Bayram Özdemir and Özdemir, 2020). Given that adolescence is a major life period marked by numerous individual and contextual challenges with the potential to impact on adolescents' mental health (Dwivedi and Harper, 2004;Grazzani Gavazzi et al, 2011), our results add to our understanding of the association between school relations and mental health across age groups, confirming that student mental health hits its lowest point during late adolescence.…”
Section: Age Invariancesupporting
confidence: 92%
“…In addition, according to the procedural justice perspective, teachers that enforce rules in a fair, respectful and transparent manner are more likely to be perceived as trustworthy and legitimate (Trinkner & Cohn, 2014 ). This dynamic can vary between students, as perceptions of teacher authority and fairness differ across children depending on both individual and experiential factors (Murray & Zvoch, 2011 ; Bayrem Özdemir & Özdemir, 2020 ; Resh, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature postulates that the teacher-student relationship significantly influences interest in the subject [50], conditions the academic trajectory of the students [36,37], and affects the academic performance of the students [33,34]. This relationship depends on the students' perception of the subject taught by the teacher and the difficulty perceived by the teacher [35].…”
Section: Discussionmentioning
confidence: 99%
“…This relationship depends on the students' perception of the subject taught by the teacher and the difficulty as perceived by the teacher [35]. These perceptions significantly influence interest in the subject matter and condition the student's future academic career [36,37]. However, a recent study states that the effects of teachers on student outcomes are generally not significant for most [38].…”
Section: Interactions In the Educational Environmentmentioning
confidence: 99%